Moral Hazard Problems in Fisheries Regulation: The Case og Illegal Landings - Frank Jensen; Niels Vestergaard (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2000)
This paper treats illegal landings as a moral hazard problem that arises, since individual catches are unobservable to society and hence private information. A tax/subsidy mechanism taking into account the asymmetric information problem is formulated as a solution to problems with illegal landings. The incentive scheme uses fish stock size as the tax variable, and can be seen as an alternative to a control policy. Rough estimates from a simulation study suggest that the incentive scheme is potentially useful. The incentive scheme also has potential application as an instrument to the solution of by-catch and discard problems.
Keywords: 330; Fischereiressourcen; Schattenwirtschaft; Theorie